1996
DOI: 10.1007/s0021663550667
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide determination by solid surface luminescence

Abstract: In the analytical system suggested, atmospheric hydrogen sulfide reacts with the surface of a filter paper treated with aqueous cadmium chloride and yields a luminescent species whose intensity can be correlated with the analyte concentration in ambient air. It was shown that the luminescent species are CdS solid particles which were formed in a well defined size. The paper luminescence was also tried on polymeric surfaces; polyethyleneoxide, polyvinyl alcohol, ethylcellulose and carboxymethylcellulose were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…It was previously demonstrated that atmospheric hydrogen sulfide reacts with the surface of a filter paper treated with aqueous CdCl 2 and yields a luminescent species whose intensity can be correlated with the analyte concentration in ambient air [7]. It has also been shown that the luminescent species is CdS solid particles which were formed in a well-defined size [7].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was previously demonstrated that atmospheric hydrogen sulfide reacts with the surface of a filter paper treated with aqueous CdCl 2 and yields a luminescent species whose intensity can be correlated with the analyte concentration in ambient air [7]. It has also been shown that the luminescent species is CdS solid particles which were formed in a well-defined size [7].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that the luminescent species is CdS solid particles which were formed in a well-defined size [7]. In this study, the similar principles were employed for signal formation using a tubular device which is familiar to most users for monitoring toxic gases in a rapid, simple and inexpensive way.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations